2013
DOI: 10.17338/trainology.2.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Isometric force production symmetry and jumping performance in collegiate athletes

Abstract: Objectives:The purpose of this study was to identify the relationship between isometric force production symmetry and jumping performance in weighted and un-weighted static and countermovement jumps (SJ and CMJ). Design: Bivariate correlation between isometric force production symmetry and vertical jump performance variables. Methods: Collegiate athletes were evaluated for this study (n=36). Subjects performed SJ, CMJ, and isometric mid-thigh pulls (IMTP). Jumps were analyzed for jump height (JH) and peak powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 19 publications
(25 reference statements)
0
72
1
Order By: Relevance
“…Yoshioka et al (2010) examined the effect of 10% bilateral asymmetries of the muscle strength on countermovement jump performance by computer simulation and found only 0.7% difference in jump height. The experimental results of Bailey et al (2013) indicate that force production asymmetry is negatively related to the bilateral vertical jumping performance and unlike the simulation study, in the real conditions the weaker leg may not be adequately compensated by the stronger leg.…”
Section: Introductioncontrasting
confidence: 60%
“…Yoshioka et al (2010) examined the effect of 10% bilateral asymmetries of the muscle strength on countermovement jump performance by computer simulation and found only 0.7% difference in jump height. The experimental results of Bailey et al (2013) indicate that force production asymmetry is negatively related to the bilateral vertical jumping performance and unlike the simulation study, in the real conditions the weaker leg may not be adequately compensated by the stronger leg.…”
Section: Introductioncontrasting
confidence: 60%
“…Between-group analyses also indicated a 'large' and significant difference between median-split fast and slow performers. Whilst previous investigations have associated asymmetries in force-related parameters with impaired athletic performance (Bailey et al, 2013;Bailey et al, 2015;Bazyler et al, 2014;Bell et al, 2014;Hart, Nimphius, et al, 2014), the relationship between asymmetry and CODS is not clear. Two investigations have noted reductions in CODS performance where an eccentric strength asymmetry is apparent (Chaouachi et al, 2012;Lockie et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…It has since been observed that the expression of vertical stiffness and associated asymmetries is highly task dependant (Maloney, Fletcher, & Richards, 2015). As a change of direction may be characterised as acyclic, ballistic and unilateral in nature, the unilateral drop jump is likely to demonstrate the greatest correspondence to CODS and may therefore carry greater validity as an assessment for vertical stiffness Several investigations have reported that asymmetries in force/power qualities may be detrimental to athletic performance (Bailey, Sato, Alexander, Chiang, & Stone, 2013;Bailey, Sato, Burnett, & Stone, 2015;Bazyler, Bailey, Chiang, Sato, & Stone, 2014;Bell, Sanfilippo, Binkley, & Heiderscheit, 2014;Hart, Nimphius, Spiteri, & Newton, 2014), however, this relationship is not clear in regards to CODS. Whilst eccentric strength asymmetry has been linked to impaired CODS in some investigations (Chaouachi et al, 2012;Lockie, Shultz, Jeffriess, & Callaghan, 2012), Lockie et al (2014) reported that athletes with 'typical' asymmetries in unilateral jump performance (vertical jump: ∼10%; horizontal jump: ∼3%; lateral jump: ∼5%) did not experience speed detriments.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the stronger limb of the asymmetrical model would make up the difference in the weaker limb and jump height would not be affected as a result. Bailey et al 5 reported different findings in a study measuring symmetry of an isometric mid-thigh pull. Their findings indicate a negative relationship exists between isometric peak force symmetry and both jump height and peak power during counter movement and static jumps.…”
Section: Introductionmentioning
confidence: 97%
“…1,2 Specifically, the relationships between force production symmetry, injury, and performance seem to be a common interest. [3][4][5] The lack of ability to produce symmetrical movement patterns and the inability to produce force symmetrically have been indicated as risk factors for injury, but currently there remains some doubt due to a lack of direct evidence to support this claim. 6,7 The role symmetry plays on performance has not been researched as extensively.…”
Section: Introductionmentioning
confidence: 99%